Effect of glutamine on leucine metabolism in humans - Hankard, R G; Haymond, M W; Darmaun, D (The American journal of physiology, 1996)
The aim of this study was to determine whether the putative protein anabolic effect of glutamine 1) is mediated by increased protein synthesis or decreased protein breakdown and 2) is specific to glutamine. Seven healthy adults were administered 5-h intravenous infusions of L-[1-14C]leucine in the postabsorptive state while receiving in a randomized order an enteral infusion of saline on one day or L-glutamine (800 mumol.kg-1.h-1, equivalent to 0.11 g N/kg) on the other day. Seven additional subjects were studied using the same protocol except they received isonitrogenous infusion of glycine. The rates of leucine appearance (RaLeu), an index of protein degradation, leucine oxidation (OxLeu), and nonoxidative leucine disposal (NOLD), an index of protein synthesis, were measured using the 14C specific activity of plasma alpha-ketoisocaproate and the excretion rate of 14CO2 in breath. During glutamine infusion, plasma glutamine concentration doubled (673 +/- 66 vs. 1,184 +/- 37 microM, P < 0.05), whereas RaLeu did not change (122 +/- 9 vs. 122 +/- 7 mumol. kg-1.h-1), OxLeu decreased (19 +/- 2 vs. 11 +/- 1 mumol.kg-1.h-1, P < 0.01), and NOLD increased (103 +/- 8 vs. 111 +/- 6 mumol. kg-1.h-1, P < 0.01). During glycine infusion, plasma glycine increased 14-fold (268 +/- 62 vs. 3,806 +/- 546 microM, P < 0.01), but, in contrast to glutamine, RaLeu (124 +/- 6 vs. 110 +/- 4 mumol. kg-1.h-1, P = 0.02), OxLeu (17 +/- 1 vs. 14 +/- 1 mumol.kg-1.h-1, P = 0.03), and NOLD (106 +/- 5 vs. 96 +/- 3 mumol.kg-1.h-1, P < 0.05) all decreased. We conclude that glutamine enteral infusion may exert its protein anabolic effect by increasing protein synthesis, whereas an isonitrogenous amount of glycine merely decreases protein turnover with only a small anabolic effect resulting from a greater decrease in proteolysis than protein synthesis.